Effect of daily calcitriol supplementation with and without calcium on disease regression in non-alcoholic fatty liver patients following an energy-restricted diet: Randomized, controlled, double-blind trial. Issue 6 (December 2017) - Lorvand Amiri, Hamid; Agah, Shahram; Tolouei Azar, Javad; Hosseini, Sharieh; Shidfar, Farzad; Mousavi, Seyedeh Neda
Summary: Background & aims: Despite evidence for beneficial effects of vitamin D, to our knowledge, no study has compared the effects of calcium supplementation with vitamin D on non-alcoholic fatty liver disease (NAFLD) regression during a hypo-energetic program. We compared the effect of the vitamin D supplementation with and without calcium on anthropometric measures and biochemical parameters in NAFLD patients during a weight-loss program. Methods: A 12-week, randomized, controlled, double-blind trial was conducted in 120 NAFLD patients randomly assigned to receive 25 μg calcitriol (n = 37), 500 mg calcium carbonate + 25 μg calcitriol (n = 37), or placebo (n = 36) every day with their lunch meals while following a weight-loss program. Results: Weight, BMI and fat mass reduction were significant in each group after 12 wk of intervention (p < 0.001), but differences among the groups was not significant after 12 wk of the study, adjusted to the baseline measurements. Significant reduction in fasting plasma glucose (FPG), insulin, insulin resistance (by HOMA-IR) and TG concentrations and an increase in HDL.C was seen over the 12 wk of study in each group (p < 0.001). Adjusting to the baseline measurements, there was significant difference in FPG (p < 0.001), HOMA-IR (p < 0.001), serum insulin (p = 0.01), TG (p = 0.01) and HDL.C (p < 0.001) among the groups after 12 wk of the study. The calcium plus calcitriol group showed a significant decrease in ALT and FPG and increase in HDL.C level compared with the calcitriol group, adjusted to the baseline measures (p < 0.001). Conclusions: Our results suggest that calcium plus calcitriol supplementation for 12 weeks may be potentially effective for biochemical parameters in NAFLD patients. Further additional larger controlled trials are needed to confirm these findings. Registration: Registered under ClinicalTrials.gov Identifier no. IRCT201408312709N29.